2012
DOI: 10.1055/s-0032-1304615
|View full text |Cite
|
Sign up to set email alerts
|

Schematherapie: Ein verhaltenstherapeutisches Konzept zur Behandlung verschiedener Persönlichkeitsstörungen

Abstract: Schema Therapy (ST) is a comprehensive approach deriving from cognitive behavioral therapy (CBT) for the treatment of chronic personality problems. ST extends CBT in 3 major issues: 1. The Schema-Mode-Model. 2. The therapeutic relationship. 3. The intensive use of experiential techniques. Schemas are persistent, rigid, and dysfunctional patterns preventing the patient from further personal emotive-interpersonal development. The central focus of the therapeutic process is the relationship between the therapist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
1
0
2
Order By: Relevance
“…Each existing psychotherapeutic model and approach is inadequate for some individuals (Norcross and Goldfried, 2005 ). Evidence-based research has demonstrated that psychotherapeutic treatments that are integrative in their nature (e.g., Interpersonal Psychotherapy, Schema Therapy, Cognitive analytic therapy) are effective for several psychiatric disorders (e.g., Depression, Post-partum depression, Social Anxiety disorders, Generalized Anxiety Disorders, Personality Disorders, Dissociative Identity) (Reay et al, 2003 ; Kellett, 2005 ; Hamidpour et al, 2011 ; Stangier et al, 2011 ; Masley et al, 2012 ; Roediger and Dieckmann, 2012 ; Clarke et al, 2013 ; Miniati et al, 2014 ).…”
Section: Why Integrative Psychotherapy Workmentioning
confidence: 99%
“…Each existing psychotherapeutic model and approach is inadequate for some individuals (Norcross and Goldfried, 2005 ). Evidence-based research has demonstrated that psychotherapeutic treatments that are integrative in their nature (e.g., Interpersonal Psychotherapy, Schema Therapy, Cognitive analytic therapy) are effective for several psychiatric disorders (e.g., Depression, Post-partum depression, Social Anxiety disorders, Generalized Anxiety Disorders, Personality Disorders, Dissociative Identity) (Reay et al, 2003 ; Kellett, 2005 ; Hamidpour et al, 2011 ; Stangier et al, 2011 ; Masley et al, 2012 ; Roediger and Dieckmann, 2012 ; Clarke et al, 2013 ; Miniati et al, 2014 ).…”
Section: Why Integrative Psychotherapy Workmentioning
confidence: 99%
“…Авторы сходятся во мнении, что интегративная психотерапия эффективна в качестве метода терапии при таких психических расстройствах, как депрессии различного генеза, тревожные расстройства, диссоциативные и другие растройства личности и т.д. (Reay et al, 2003;Kellett, 2005;Hamidpour et al, 2011;Stangier et al, 2011;Masley et al, 2012;Roediger, Dieckmann, 2012;Clarke et al, 2013;Miniati et al, 2014); интегративный подход позволяет лучше адаптировать терапию к особенностям и потребностям каждого клиента; в рамках интегративной психотерапии техники не применяются к пассивному клиенту, клиент рассматривается как активный участник сессий, в ходе которых терапевт представляет возможные альтернативные варианты вbдения себя или ситуаций, позволяющие скорректировать негативный опыт клиента.…”
Section: резюмеunclassified
“…Авторы сходятся во мнении, что интегративная психотерапия эффективна в качестве метода терапии при таких психических расстройствах, как депрессии различного генеза, тревожные расстройства, диссоциативные и другие растройства личности и т.д. (Reay et al, 2003;Kellett, 2005;Hamidpour et al, 2011;Stangier et al, 2011;Masley et al, 2012;Roediger, Dieckmann, 2012;Clarke et al, 2013;Miniati et al, 2014); интегративный подход позволяет лучше адаптировать терапию к особенностям и потребностям каждого клиента; в рамках интегративной психотерапии техники не применяются к пассивному клиенту, клиент рассматривается как активный участник сессий, в ходе которых терапевт представляет возможные альтернативные варианты вbдения себя или ситуаций, позволяющие скорректировать негативный опыт клиента.…”
Section: резюмеunclassified